PEGylation of Albumin Nanoparticles Immobilized with the Anti-Tuberculosis Drug “Isoniazid” - Galiyeva, A.R.; Tazhbayev, Y.M.; Yessentayeva, N.A.; Daribay, A.T.; Marsel, D.T.; Sadyrbekov, D.T.; Zhaparova, L.Zh.; Arystanova, Zh.T. (Karagandy University of the name of acad. E.A. Buketov, 2023)
Polyethylene glycol (PEG) is widely used in nanomedicine to extend the circulation time of a drug in the blood and increase drug efficacy. Conjugation by attaching polyethylene glycol to an albumin macromolecule and nanoparticles is a well-established technique known as PEGylation. The aim of this research was to prepare and evaluate serum stable long circulating PEG-albumin-isoniazid nanoparticles for the treatment of Mycobacterium tuberculosis which can improve its therapeutic effect by increasing its permeability, solubility and accumulation in aveolar macrophages. For the first time, PEGylated BSA nanoparticles loaded with isoniazid were synthesized by desolvation using urea and cysteine as denaturing and stabilizing agents. Nanoparticles with an average size of up to 300 nm were obtained by varying the PEG concentration. The polydispersity index of all particle charges was less than 0.1, indicating monodisperse size. The ζ potential values indicate sufficient physical stability of the nanoparticles. SEM images showed that the particles were spherical in shape. The TGA and DSC results obtained confirm that drug loading does not affect the structure of the polymer. Based on FT-IR studies, the absence of chemical interactions between PEGylated BSA nanoparticles and isoniazid was established. In in vitro release studies, the nanoparticles were demonstrated to have a prologue release.
Keywords: nanoparticles; bovine serum albumin; polyethylene glycol; isoniazid; desolvation; hydrophilic drugs; anti-tuberculosis drugs